Unrecognized diversity and distribution of soil algae from Maritime Antarctica (Fildes Peninsula, King George Island) - Rybalka, Nataliya; Blanke, Matthias; Tzvetkova, Ana; Noll, Angela; Roos, Christian; Boy, Jens; Boy, Diana; Nimptsch, Daniel; Godoy, Roberto; Friedl, Thomas (Frontiers in Microbiology, 2023)
Introduction Eukaryotic algae in the top few centimeters of fellfield soils of ice-free Maritime Antarctica have many important effects on their habitat, such as being significant drivers of organic matter input into the soils and reducing the impact of wind erosion by soil aggregate formation. To better understand the diversity and distribution of Antarctic terrestrial algae, we performed a pilot study on the surface soils of Meseta, an ice-free plateau mountain crest of Fildes Peninsula, King George Island, being hardly influenced by the marine realm and anthropogenic disturbances. It is openly exposed to microbial colonization from outside Antarctica and connected to the much harsher and dryer ice-free zones of the continental Antarctic. A temperate reference site under mild land use, SchF, was included to further test for the Meseta algae distribution in a contrasting environment. Methods We employed a paired-end metabarcoding analysis based on amplicons of the highly variable nuclear-encoded ITS2 rDNA region, complemented by a clone library approach. It targeted the four algal classes, Chlorophyceae, Trebouxiophyceae, Ulvophyceae, and Xanthophyceae, representing key groups of cold-adapted soil algae. Results A surprisingly high diversity of 830 algal OTUs was revealed, assigned to 58 genera in the four targeted algal classes. Members of the green algal class Trebouxiophyceae predominated in the soil algae communities. The major part of the algal biodiversity, 86.1% of all algal OTUs, could not be identified at the species level due to insufficient representation in reference sequence databases. The classes Ulvophyceae and Xanthophyceae exhibited the most unknown species diversity. About 9% of the Meseta algae species diversity was shared with that of the temperate reference site in Germany. Discussion In the small portion of algal OTUs for which their distribution could be assessed, the entire ITS2 sequence identity with references shows that the soil algae likely have a wide distribution beyond the Polar regions. They probably originated from soil algae propagule banks in far southern regions, transported by aeolian transport over long distances. The dynamics and severity of environmental conditions at the soil surface, determined by high wind currents, and the soil algae’s high adaptability to harsh environmental conditions may account for the high similarity of soil algal communities between the northern and southern parts of the Meseta.